The Influence of Acid Whey on the Lipid Composition and Oxidative Stability of Organic Uncured Fermented Bacon after Production and during Chilling Storage - Anna Okoń; Piotr Szymański; Dorota Zielińska; Aleksandra Szydłowska; Urszula Siekierko; Danuta Kołożyn-Krajewska; Zbigniew J. Dolatowski (MDPI AG, 2021)
The aim of this research was to evaluate the effect of acid whey on changes in the fatty acid profile, oxidative stability, physico-chemical parameters, and microbiological and sensory quality of traditional organic uncured fermented Polish bacon after production and during chilling storage. Three different treatments of fermented bacon were produced: C-control bacon with a nitrite curing mixture; T-bacon with a nitrate curing mixture; and AW-bacon with acid whey and NaCl. The acid whey used in the production of uncured fermented pork bacon positively changed the sensorial characteristics, directly after the ripening process, and had a positive effect in terms of a decrease in the pH of the product. All of the fermented bacon treatments in general were of good microbiological quality. A higher lactic acid bacteria (LAB) level was observed in the AW treatment after the fermentation process, and the bacteria number did not change during storage, whereas in the C and T treatments, the LAB level increased during storage (p < 0.05). The application of acid whey did not limit the formation of secondary oxidation products (TBARS) during bacon ripening (1.68 mg MDA kg−1), but had a reduced value during storage time (0.73 mg MDA kg−1). The highest polyunsaturated fatty acid (PUFA) levels, after ripening and after four weeks of refrigerated storage, were found in the C treatment. In the AW treatment, it was found that the PUFA level increased; likewise, the content of n-3 and n-6 fatty acids increased, while saturated fatty acids (SFAs) decreased during storage (p < 0.05). The opposite tendency was observed in the C treatment. After four weeks of storage, the PUFA/SFA ratio was the lowest in the nitrate treatment, and higher values of the PUFA/SFA ratio were obtained in the acid whey and nitrite treatment (p < 0.05).